Woody veins: A disease of Peepal (Ficus religiosa)? - AHLAWAT, Y.S. (Indian Phytopathology, 2017)
Ficus religiosa or Peepal is a sacred tree native to Nepal, India, Bangladesh, Myanmar, Pakistan, Sri Lanka, south-west China and Indochina. It is also known as the bodhi tree, pippala tree, peepal tree or ashwattha tree (in India and Nepal). Ficus religiosa is a large dry season-deciduous or semi-evergreen tree up to 30 meters (98 ft) tall and with a trunk diameter of up to 3 meters (9.8 ft). As an interesting fact, the leaves of this tree move continuously even when the air around is still and no wind is blowing. This phenomenon can be explained due to the long leaf stalk and the broad leaf structure. However, religious minded people in Hindu/Buddhist religion attribute this movement of the leaves to the fact that â€œdevasâ€ or â€œgodsâ€ reside on these leaves and make it move continuously. This fact is also mentioned in the Bhagavad Gita as a verse â€œO Ashvatha, I honour you whose leaves are always movingâ€ Ficus religiosa is used in traditional medicine for about 50 types of disorders including asthma, diabetes, diarrhea, epilepsy, gastric problems and inflammatory disorders. Several peepal trees in Dwarka, New Delhi have been observed with woody vein of leaves (Fig. 1). Up to 60% of leaves of infected trees showed woody vein. Such leaves also showed mosaic mottling. Some leaves showed vein woodyness only one or two veins while other showed all the veins with woody symptoms. I am reporting this disorder as it appears concern to our religious tree with the hope that working scientists will investigate the etiology of this disease.